YIELD OF COLLAGEN EXTRACTED FROM FRESHWATER MUSSEL SHELL (Pilsbryoconcha sp.) OF RIVER AND POOL WATERS - Pipit Pasaribu; N. Ira Sari; Dian Iriani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This study aims to determine the yield of freshwater mussel shell collagen from river and water pool waters. The parameter measured is the yield value of collagen. The research method used was experimental, namely making collagen from mussel shells obtained from river and pond waters in Kampar Regency. Then a comparison of the collagen content contained in the shells of river and pond mussels was carried out. The data obtained were analyzed using the T-test, namely the comparison with two treatments. The results of this study indicate that the highest yield of collagen produced from river mussel shells is 18.76% with0.50 Macetic acid and 18.73% deep mussel shells with 0.75M acetic acid.Keywords: Collagen, Pilsbryoconcha sp., Acetic Acid, Yield